Relationship between breastfeeding frequency and breast milk production in breastfeeding mothers at TPMB Tias Yuniasri Maesan Bondowoso - Ulfatul Hasanah; Anik Sri Purwanti (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Breast milk production is a key determinant in the success of exclusive breastfeeding, and one of the main influencing factors is breastfeeding frequency. Increased breastfeeding frequency stimulates the release of prolactin and oxytocin hormones, which support milk production and ejection; however, in practice, some mothers still breastfeed infrequently, leading to suboptimal milk production. This study aimed to analyze the relationship between breastfeeding frequency and breast milk production among breastfeeding mothers at TPMB Tias Yuniasri Maesan, Bondowoso. The study used a correlational analytic design with a cross-sectional approach. The population consisted of breastfeeding mothers with infants aged 0–6 months (n = 45), and a sample of 30 respondents was selected using purposive sampling. The independent variable was breastfeeding frequency, while the dependent variable was breast milk production. Data were collected using questionnaires and observation sheets and analyzed using the Spearman Rank test with a significance level of α = 0.05. The results showed that most respondents had frequent breastfeeding (60%) and smooth breast milk production (66.7%). Statistical analysis indicated a strong and significant relationship between breastfeeding frequency and breast milk production (r = 0.782; p = 0.000). In conclusion, higher breastfeeding frequency is associated with better breast milk production, and health workers are recommended to strengthen lactation education and counseling to encourage optimal breastfeeding practices in support of exclusive breastfeeding programs.